Bee Honey as a Bioindicator of Environmental Pollution with Some Heavy Metals in Zawia and Janzour Regions, Libya - Alzagtat, Ahmeda A.; Alsury, Alsury A. (Al-Mukhtar Journal of Sciences, 2023)
This study aims to estimate the concentration of some heavy metals in bee honey and its various products and the possibility of inferring bees as a bioindicator in determining pollution by these metals. Eight hives were distributed; seven were close to different sources of pollution and one hive was in an agricultural site far control sample. Twenty honey samples were collected from the mentioned sites during three seasons and some samples of pollen, wax, and gum were also collected from one of the sites of pollution sources and the control site. Obtained results indicated that most of the honey samples were above the permissible limit for lead and cadmium compared to the European Union (EU) standard (1.0) mg/kg and the Codex standard. It was found that all samples contained relatively high concentrations of lead and cadmium in all sites. As for copper and zinc, all samples contained concentrations less than the permissible limit according to the Codex standard, which is (5.0) mg/kg. As for the concentration of these elements in pollen, wax, and gum samples, the highest concentration was in bee gum samples. It became clear through the results of this study those bees, and through their various products: honey, pollen, beeswax, and gum, can be consider a bioindicator of the environment to determine the extent of pollution by some heavy metals in the sites surrounding the beehives.